The Child Quantity–Quality Trade-off - Rufei Guo; Junjian Yi; Junsen Zhang (Institute of Labor Economics (IZA), 2022)
This chapter reviews the growing literature on the child quantity–quality (QQ) trade-off. During the transition from the traditional agricultural economy to modern economic growth, household real income increases, fertility decreases, and human capital investment per child increases. Motivated by this observation, economists started to develop theoretical models of the child QQ trade-off in the 1970s. Macroeconomic models that theoretically incorporate the QQ trade-off flourish. As a parallel development, empirical studies exploit multiple sources of exogenous variations in family size, such as twin births, child sex composition, and family planning policies, to identify the causal effect of fertility on child quality. Dialogues between theoretical and empirical analyses should empower future research on the child QQ trade-off.
Keywords: D10; J13; 330; demographic transition; fertility; child human capital investment; child quantity-quality trade-off